Komitmen organisasi pada karyawan: Bagaimana peranan psychological well being? - Zulviarrachma Nuril Ariva; Eben Ezer Nainggolan; Sayidah Aulia Ul Haque (INNER: Journal of Psychological Research, 2023)
The purpose of this study was to determine the relationship between psychological well-being and organizational commitment to employees. This study used correlational quantitative research with a total of 106 respondents. The sampling technique used in this research is the purposive sampling technique. The criteria used in this study are men or women aged 17-60 years who are working in a company. The analysis technique used is the Parametric Test. Based on the results of data analysis using the Simple Linear Regression Test, a correlation value or relationship is obtained, meaning that there is a significant positive relationship between psychological well-being and organizational commitment to employees. Keywords: organizational commitment, psychological well-being, employees.